GO-TO-MARKET STRATEGY FOR PROITIVITY TO ENTER IT EDUCATIONAL SECTOR IN KAZAKHSTAN AND ABROAD - Toktagulova, Aigerim; Kartbayev, Almas; Zhaparova, Aray; Tkachenko, Natalia; Dilixiati, Rena (Nazarbayev University Graduate School of Business, 2024)
The current digital era dictates its own rules with the demand for experienced IT professionals, driven by the rapid development of technology in all industries. To solve this problem, the Government of Kazakhstan has launched the TechOrda program, intending to train 100,000 IT specialists by 2025. The newly established ProITivity School of Information Technology joined this mission by receiving vouchers from the government for free tuition. However, given that the program ends next year and the number of vouchers is limited, ProITivity recognizes the need for a more sustainable and diversified strategy. This project explores how ProITivity can abandon its dependence on government funding and enter the B2B and B2C markets, targeting adult and younger students throughout Kazakhstan and abroad. The main goal is to develop a market entry strategy that positions ProITivity as a leading provider of IT education services, even though it goes beyond government support. The main areas of work include identifying competitive advantages, improving customer segmentation, and developing a pricing model that considers both short-term and long-term goals. Initial results show that Kazakhstan represents an attractive but competitive market landscape, where numerous providers of EdTech services already work in educational institutions. Competitor analysis identifies gaps in specific training modules, and pricing analysis points to potential entry points. Two strategies are proposed based on a deep primary and secondary data analysis. The first is to keep and promote the same product with different marketing approaches. The second is updating the product so alumni are more experienced. Ultimately, these strategies will allow ProITivity to grow steadily and contribute to the development of Kazakhstan's digital workforce while exploring opportunities to expand the availability of IT education outside the country.
Keywords: Type of access: Embargo; Go-to-market strategy; marketing; PESTEL; TECHNOLOGY::Civil engineering and architecture::Surveying; interview; IT educational sector; EdTech